Allied health assistants' perspectives of their role in healthcare settings: A qualitative study. (10th June 2022) - King, Olivia A.; Pinson, Jo‐Anne; Dennett, Amy; Williams, Cylie; Davis, Annette; Snowdon, David A.
Abstract: Allied health assistants (AHAs) are important members of the health workforce and key to meeting population health needs. Previous studies exploring the role and utility of AHAs from multiple stakeholder perspectives suggest AHAs remain poorly utilised in many healthcare settings. This qualitative study explores the experiences and perspectives of AHAs working in healthcare settings to determine the contextual factors influencing their role, and mechanisms to maximise their utility. We conducted semi‐structured interviews using purposive sampling with 21 AHAs, from one regional and three metropolitan health services in Australia, between February and July 2021. We used a team‐based framework approach to analyse the data. Four major themes were identified: 1) AHAs' interpersonal relationships, 2), clarity and recognition of AHA roles and role boundaries, 3) AHAs accessing education and professional development, and 4) the professional identity of the AHA workforce. Underpinning each of these themes were relationships between AHAs and other healthcare professionals, their patients, health services, and the wider AHA workforce. This study may inform initiatives to optimise the utility of AHAs and increase their role in, and impact on, patient care. Such initiatives include the development and implementation of guidelines and competencies to enhance the clarity of AHAs' scope of practice, the establishment of standardised educational pathways for AHAs, and increased engagement with the AHA workforce to make decisions about their scope of practice. These initiatives may precede strategies to advance the AHA career structure.